An approach to the discourses and practices of the Active School in Colombia - Gutierrez, Luz Andrea; Mariño, Liliana Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
A theoretical-reflexive construction is presented as the state of the art of the Active School in Colombia, which is part of the project: Active School, an experience of transformative education. Its transformations, discourses and practices, are identified from the study of digital articles in Publindex. Five categories are defined: Theoretical configuration of the model, History of the New School in Colombia, Curriculum, Methodology and Applications and experiences, which emerge from a descriptive methodology, based on theoretical reflections and on the development of both a matrix for data analysis and subject sheets—the latter allowed to find other relevant categories and an interrelation between different subcategories. There is evidence of the historical appropriation of the model, its positive effects, flaws, tendencies, practices, and research gaps around the Active New School program in the country.